2007
DOI: 10.1002/adsc.200700221
|View full text |Cite
|
Sign up to set email alerts
|

A Practical and Versatile Access to Dihydrosalen (Salalen) Ligands: Highly Enantioselective Titanium In Situ Catalysts for Asymmetric Epoxidation with Aqueous Hydrogen Peroxide

Abstract: A modular synthesis for chiral and nonsymmetrical salalen ligands (i.e., mono-reduced salens), carrying an imine and an amine functionality has been developed. The ligands can be assembled in situ by Schiff base formation of an N-(2-hydroxybenzyl)diamine with a salicylic aldehyde, thus allowing rapid and easy variation/optimization of the ligand structure. Aiming at optimal activity and enantioselectivity in the titanium-catalyzed asymmetric epoxidation of non-functionalized olefins, a positional scanning of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(25 citation statements)
references
References 29 publications
0
24
0
Order By: Relevance
“…Since asymmetric Schiff base ligands have many advantages over their symmetrical counterparts in the composition and geometry of transition metal complexes and properties, salens are privileged ligands for application in asymmetric catalysis. Also, salen metal complexes have been successfully used as catalytic species in numerous organic transformations [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Since asymmetric Schiff base ligands have many advantages over their symmetrical counterparts in the composition and geometry of transition metal complexes and properties, salens are privileged ligands for application in asymmetric catalysis. Also, salen metal complexes have been successfully used as catalytic species in numerous organic transformations [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The biarylbridged salalen ligands could be easily prepared from monoalkylated diamine II and 3,3Ј-diformyl-2,2-dihydroxy-1,1Ј-biphenyl or 3,3Ј-diformyl-2,2-dihydroxy-(R)-1,1Ј-binaphthyl according to the procedures for the synthesis of monomeric salalen ligands. [28,29] Based on this strategy, biaryl-bridged salalen ligands 1-4 were readily synthesized ( Figure 1). A desired di-μ-oxotitanium complex could be formed with a standard procedure reported by Katsuki et al, which was confirmed by ESI-TOF MS ( Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Based on their findings, Katsuki and Berkessel favored a mononuclear titanium complex as the real species responsible for the epoxid- ation reaction. [24,28,29] As for another breakthrough in designing new ligands for asymmetry reaction, Ding and co-workers developed binuclear Ti-salen catalysts connected through organic linkages to dramatically enhance the catalytic activity and enantioselectivity for the cyanation of aldehydes. [40] Inspired by this pioneering work and our early work in asymmetric reactions, [30,41] we decided to bridge two salalen ligands with a biaryl linker and to synthesize their corresponding di-μ-oxotitanium complexes.…”
Section: Introductionmentioning
confidence: 99%
“…Transition metal titanium has been widely taken as active species for epoxidation reactions [3]. Although many catalytic epoxidation reactions using homogeneous catalysts have been successfully demonstrated [4][5][6][7][8][9][10], the difficulties in separating of the catalysts greatly restrict their applications in practice. Titanium-containing mesoporous molecular sieves have been used as efficient heterogeneous catalysts in the epoxidation of alkenes [11,12].…”
Section: Introductionmentioning
confidence: 99%